Konsep Dasar Desentralisasi Pendidikan Non-Formal Berdasarkan Undang-undang Nomor 20 Tahun 2003 Tentang Sistem Pendidikan Nasional - La Syarifuddin (Jurnal Risalah Hukum, 2010)
Non-formal education as mentioned in Pasal 1 angka 12 UU Nomor 20 Tahun 2003 is the path of education outside the formal education that can be implemented in a structured and tiered. Non-formal education referred to out of school education or community education, it is more flexible than formal education. Non-formal education serves to develop students' potentials with emphasis on the acquisition of knowledge and functional skills and to develop professional attitude and personality. The basic concept of non-formal education decentralization in UU Nomor 20 tahun 2003 is getting even distribution on education and an alternative for the poor peoples who do not or have not had time to obtain formal education.